Intraabdominal adhesion formation is associated with differential mRNA expression of metabolic genes PDHb and SDHa - Wallwiener, Markus; Wallwiener, Christian Wilhelm; Molinas, Roger (Archives of gynecology and obstetrics, 2012)
PurposeIntraabdominal adhesions represent a major cause of postoperative morbidity potentially causing pain, small bowl obstruction and infertility. The process of adhesion formation might be regarded as an ischemic disease. Under hypoxic conditions, metabolic enzymes are regulated via hypoxic responsive elements by the hypoxia-inducible factor 1 (HIF-1). We therefore investigated the gene expression of HIF-1 and two pivotal metabolic genes, pyruvate-dehydrogenaseβ (PDHb) and succinate-dehydrogenase-complex-subunit-A (SDHa) in a validated ischemia model of adhesion formation.MethodsPeritoneal adhesions were created using an ischemic button model in female Wistar rats. Expression levels of HIF-1α/β, PDHb and SDHa in adhesiogenic versus native peritoneum were analyzed using quantitative PCR on the third post-operative day.ResultsGene expression of HIF-1α was up-regulated by 10 % (p = 0.003), PDHb was up-regulated by 23 % (p = 0.0004) and SDHa (p = 0.0005) was up-regulated by 24 % in the adhesiogenic peritoneum compared to native peritoneum. The expression level of HIF-1β was not significantly influenced by adhesion formation.ConclusionThe increased expression level of HIF-1α in the peritoneal tissue of ischemic buttons associated with postsurgical adhesions supports the major role for hypoxia in influencing peritoneal expression patterns of genes involved in the process of adhesion formation. As pivotal metabolic genes are upregulated, this seems to be an anabolic process associated with increased cellular metabolism.
Gesehen am 31.10.2018